Leading for sustainability: an exploratory study of founder transitions in nonprofit organisations in the Western Cape - Kempster, Michelle (Department of Social Development, 2020)
The sustainability of the nonprofit sector is vital to social development in South Africa. The sector plays a significant role in the provision of social protection and developmental services to the most vulnerable citizens of our country. Nonprofit organisations operate in an environment which is often complex, volatile and uncertain. With the increasing demand for accountability, sound governance and ever more creative fundraising models, leading and managing nonprofits has become particularly challenging. Most nonprofits survive infancy because of the incredible passion and commitment of nonprofit founders, towards their unwavering belief in a social cause. Without their energy and charisma, the nonprofit sector would not be as influential and substantial as it is today. For an organisation to mature and increase its desired impact, the founder energy needs to be refined and combined with new skills that suit a larger and more effective organisation. However, if this does not happen, some organisations become dependent on the founder, causing risk of trauma, stagnation or demise, particularly when the founder moves on. Even where an organisation remains in operation, a founder transition may result in unnecessary damage to all stakeholders, if not planned and managed well. Founder transitions in nonprofit organisations has not been given the recognition in South African literature that it deserves. Therefore, the purpose of this study is to answer the question, “How do nonprofit organisations in South Africa experience founder transitions?” In this study, an exploratory qualitative research design was used in order to gain a deeper understanding of the experience of founder transitions in nonprofit organisation. Based on a literature review on founder transitions and related succession planning and founder’s syndrome in the nonprofit sector, the research questions and a research methodology were chosen. Ethics clearance was given by the University of Cape Town and a sample of 17 participants were selected to take part in the study by purposive sampling. The participants, all senior leaders in the nonprofit sector with experience of founder transitions, represented eight organisations in the Western Cape. The data was collected using a semi-structured interview schedule, and analysed using Tesch’s (1990) steps of data analysis. The contribution this study makes is to add to the understanding of the founder transition planning and management practices of South African nonprofit organisations, exposing both the opportunities and challenges experienced during the transition. The study makes a number of findings including: 1) the level of risk and challenge to nonprofit organisations during the founder transition is underestimated by their leaders, 2) nonprofit leaders feel they are ill equipped to manage founder transitions effectively, 3) founder transitions are a particularly emotional experience requiring relationships to be managed skillfully, 4) succession planning is a neglected risk management practice, impacting on the magnitude of the founder transition, 5) nonprofit founders and boards are not certain of their distinct roles during the founder transition, which can result in poor leadership and management of the founder transition, and 6) effective founder transitions constitute an additional cost to nonprofit organisations which should be budgeted for. Based on these findings, the study concludes with recommendations for nonprofit boards on how to improve the planning and management of founder transitions in nonprofit organisations.